2013
DOI: 10.1038/nature12655
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus δ-toxin induces allergic skin disease by activating mast cells

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that affects 15 to 30% of children and ~5% of adults in industrialized countries1. Although the pathogenesis of AD is not fully understood, the disease is mediated by an abnormal immunoglobulin E (IgE) immune response in the setting of skin barrier dysfunction2. Mast cells (MCs) contribute to IgE-mediated allergic disorders including AD3. Upon activation, MCs release their membrane-bound cytosolic granules leading to the release of multiple molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
430
1
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(452 citation statements)
references
References 35 publications
8
430
1
13
Order By: Relevance
“…5B). The large difference in G-CSF agrees with previously reported effects of one of the PSMs, ␦-toxin, on mast cell degranulation and G-CSF release (44). Differences in circulating IL-6 and IL-1␤, both of which are released from keratinocytes, were also noted (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…5B). The large difference in G-CSF agrees with previously reported effects of one of the PSMs, ␦-toxin, on mast cell degranulation and G-CSF release (44). Differences in circulating IL-6 and IL-1␤, both of which are released from keratinocytes, were also noted (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Eight days after the start of treatment with tamoxifen or vehicle, mice were patched with OVA-DQ (Life Technologies) for 30 hours to assess OVA uptake and processing, with a protocol adapted from Geha and collaborators (83), but without tape stripping. OVAthought also to contribute to human AD (47,48,(74)(75)(76)(77), and that shares striking similarities with our Rabgef1 K-KO mice (see Figure 10), we showed that significant reductions in levels of RABGEF1 protein were observed by immunohistochemistry in HDM/SEBsensitized and challenged mouse skin, as compared with control skin. These findings clearly show that the induction of cutaneous allergic inflammation in WT mice is associated with significant reductions in levels of keratinocyte RABGEF1 in the induced skin lesions.…”
Section: Discussionsupporting
confidence: 50%
“…Overgrowth of and infection with S. aureus are both contributors to and consequences of the immune imbalance and poor barrier function characteristic of AD. S. aureus can directly activate allergic mast cells (8,9) and T cells (10). Treatment with antibiotics can reduce S. aureus burdens and improve symptoms but does not normalize the underlying pathology (2).…”
Section: Resultsmentioning
confidence: 99%